The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.31235/osf.io/nf9ms
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Central banking, shadow banking, and infrastructural power

Abstract: Public monetary governance and private market practices are closely entangled. Monetary policy depends on private financial infrastructures. At the same time, central banks exert considerable influence on market structures and practices. This paper presents the theoretical rationale for analyzing state-finance interactions through the lens of infrastructural entanglement and infrastructural power. We then apply this perspective to two crucial cases, showing how and why the Federal Reserve and the European Cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 47 publications
(68 reference statements)
0
23
0
1
Order By: Relevance
“…The need for safe-assets (bonds) to serve as collateral for shadow money creation has lowered yields on sovereign debt repo with clear implications for 25 governments as well as other market participants. An extended model of sovereign bond holders should then not only distinguish between foreign and domestic, but also consider the role that shadow banks as bond holders play in the dynamics of market discipline, structural and infrastructural power (Braun and Gabor, 2019). Finally, it would be interesting to assess whether governments' interpretations of 'what investors want' is more accurate for different investor groups.…”
Section: Resultsmentioning
confidence: 99%
“…The need for safe-assets (bonds) to serve as collateral for shadow money creation has lowered yields on sovereign debt repo with clear implications for 25 governments as well as other market participants. An extended model of sovereign bond holders should then not only distinguish between foreign and domestic, but also consider the role that shadow banks as bond holders play in the dynamics of market discipline, structural and infrastructural power (Braun and Gabor, 2019). Finally, it would be interesting to assess whether governments' interpretations of 'what investors want' is more accurate for different investor groups.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, during the euro crisis EU authorities protected the status of bonds as safe assets to secure the operation of interbank lending. For its part, by continuing to accept bonds as collateral and using them to conduct monetary policy (Braun and Gabor 2019), the ECB also contributes to making them safe. All this runs counter to the very logic of market discipline based on the principle of creditor risk.…”
Section: The Problem Of the Sovereignmentioning
confidence: 99%
“…The second contribution derives from here. As recent studies have shown, central banking requires mobilising private infrastructures with oftentimes highly contingent outcomes (Walter and Wansleben 2019, Braun and Gabor 2020, Dutta 2020. By extending this line of analysis to the international level, this article locates the politics of swap interventions in the infrastructural problem of what makes the global dollar system 'governable' from the perspective of the Federal Reserve.…”
Section: Introductionmentioning
confidence: 96%